Mobile Reservation System for Hotels in Malaysia - Malee, Nojeera (2009)
Wireless Networks and mobile computing had been explored growth up, millions of users and explores its usage in many ways depend on their desire to fulfill their needs. As can see for instance a traveler (tourist or a businessman) has to travel quite frequently to the different places around the world. One of the technologies used called WAP (Wireless Application Protocol) has enabled mobile service providers to offer another step forward the promise of mobility to its customers in a very useful way. Hotels operate around the clock or 24 hours a day to fulfill traveler's demand and providing an excellent service to their customers in all areas. It is envisaged that the objectives of my paper are: I. to design the system requirements for Mobile Hotel Reservation System (MHRS) for Hotels in Malaysia that will include all information of hotels; II. to develop MHRS in Malaysia which will help tourists find accommodations, hotels and any related information from the convenience of their mobile devices; III. to propose new and useful system or tools by the use of mobile devices for hotels reservation in Malaysia; and iv. to facilitate travelers with a self service system for hotel reservation. As travelers are always on the move, so should be with hoteliers to adopt new technologies to get a hold of customers' attention and make it easy and satisfaction for them.